The Qur'anic Method of Formulating Supplications among the People of the House, Peace Be Upon Them: An Analytical Study (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The Qur'anic method of formulating supplications among the People of the House (peace be upon them) is the focus of this analytical study. The summary of the Holy Qur'an represents the divine revelation bestowed upon the Seal of the Prophets, Muhammad bin Abdullah (may God's prayers and peace be upon him). It is a discourse rich in meaning and style that is frequently cited within the Qur'an. The Qur'an serves as the foundation of living Islam and stands as an eternal miracle that has challenged humanity throughout the centuries and continues to do so today.The Holy Qur'an conveys God's message to all of humanity, as emphasized in multiple verses, including the proclamation of God Almighty: "Blessed is He who sent down the Criterion to His servant so that he may be a warner to the worlds" (Al-Furqan: Verse 1).In regard to supplication, it is both the means and weapon of the believer. The Messenger of Allah, Muhammad (may Allah's peace and blessings be upon him), said: "Shall I not guide you to a weapon that will save you from your enemies and ensure your livelihood?" Upon receiving affirmation, he added, "You call on your Lord night and day, for the weapon of the believer is prayer."The Ahl al-Bayt (peace be upon them) approached the Holy Qur'an, especially in the context of the verse of purification, as narrated by the Prophet (peace and blessings be upon him). Additionally, the Al-Sahifa Al-Sajadiyah serves as a collection of traditional supplications attributed to Imam Al-Sajjad, Zain al-Abidin Ali bin Al-Hussein bin Ali bin Abi Talib, one of the Imams of the Ahl al-Bayt, whom Allah has purified and from whom He has removed all impurities. He is recognized as the fourth Imam of the Ahl al-Bayt (peace and blessings be upon them).